DIALEKTIKA ISLAM DAN BUDAYA LOKAL JAWA - Andik Wahyun Muqoyyidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This article reveals the Islamic cultural problems which spreadsand develops in Indonesia especially those which are related to Islam andJavanese culture dialectic. This idea refers to cultural-sociological framewhich dominated more in the form of acculturation. Although there was afluctuated development in the 19’s still acculturation dominated almostall religion’s expression in Java. Syncretism and religion tolerance becamethe character of Islam in Java and this was based to Javanese contextanimism and Hinduism.